Mathematical Learning Development using Discovery Learning Model to Improve Mathematical Understanding Skills of Students - Yuni Kartika; Nahor Murani Hutapea; Kartini Kartini (Journal of Educational Sciences, 2020)
This study aims to produce a mathematics learning tool with a discovery learning model on rectangular and triangular material, with valid, practical and effective criteria to improve the mathematical understanding ability of grade VII students in junior high school. The type of research was development research with the design development using Borg and Gall. This study produced learning tools consisting of syllabus, lesson plans and student worksheets (LKPD). The results of the study showed that the learning tools met valid, practical and effective criteria. The validity of the product development was determined by expert validation with an average value of 4.46 with a very valid category. The practicality of the product development is determined by the teacher with an average of 99%, students 90.57% and observers 4.16 which is categorized as very practical while the effectiveness of the development product in terms of the achievement of learning objectives using KKM scores of 75 is obtained from the test results of mathematical understanding ability with the results there is an increase in learning outcomes using developed learning tools.